Comportements Reproductifs Des Jeunes Femmes A Bafia Au Cameroun - Didier Nganawara; H. Blaise Nguendo Yongsi (European Scientific Journal, ESJ, 2017)
Background: With regard to sexual and reproductive health policies, the young are usually a target population. In fact, reproductive behaviours of young people often constitute a matter of public health concern, as their well-being is hampered by early and unwanted pregnancies, unsafe abortions along with complications, HIV/AIDS. Objective: This study aims at providing a better insight into reproductive behaviours of two groups of women (15-24 years and 25-34 years) in Bafia, and to link them with their cultural, economic, and socio-demographics characteristics. Results: The analyses performed show that women aged 15-24 years enter prematurely the sexual and fertile life more than those aged 25-34 years. For those who are still singles, the mean age at first pregnancy is 17,7 years for women aged 15-24 years versus 20,1years for those aged 25-34 years. And as for married women, the mean age at first pregnancy is respectively of 17,6years versus 19,4 years. However, women aged 15-24 years get married more lately than those aged 25-34 years. Conclusion: Although the level of knowledge of the contraceptive methods of women aged 25-34 years is too high than those aged 15-24 years, it appears that the older age-class (25-34 years) resort less to contraceptive methods than the younger old-class (15-24 years), whatever their matrimonial status. However, the standard of life and level of education act in an indisputable on those indicators.